Pelatihan Pengolahan Limbah Organik Rumah Tangga dengan Budidaya Maggot Black Soldier Fly (BSF) kepada IRT RT 08 RW 14 Jatisampurna, Kota Bekasi - Wahyuningrum, Maria Aditia; Suryani, Suryani; M. Sholihah, Siti; Muhdiana, Ludi; Romayanti, Angelina; Alifya, Adila Tsabita (Jurnal Pelayanan dan Pengabdian Masyarakat (Pamas), 2026)
Household organic waste management in Indonesia remains a serious challenge, with food scraps being the largest component of waste. Limited knowledge among the community, particularly housewives, about effective and economically valuable processing methods is a major challenge. This study aims to empower housewives in RT 08 RW 14 Jatisampurna, Bekasi City through Black Soldier Fly (BSF) maggot cultivation training as a solution for organic waste bioconversion. The activity was carried out from June to September 2025. The methods used were counseling, training, and practical mentoring. The results of the activity showed a 76% increase in participant knowledge based on pre- and post-activity tests. The "Maggot Box" innovation provided was successfully implemented by 30 housewife participants, who are now able to process organic waste independently. The perceived benefits include reducing waste volume, increasing economic value through by-products (animal feed from maggots), and increasing the role of housewives in environmental management. This activity is effective in providing practical and sustainable solutions to organic waste problems while increasing community productivity